PENGARUH POSISI KERJA SECARA ERGONOMI TERHADAP PENINGKATAN PRODUKTIVITAS KERJA PETUGAS ADMINISTRASI DI RUMAH SAKIT ISLAM KARAWANG - Muhidin, Muhidin; Jumaedi, Jumaedi; Chaerani Tri Yuliana; Wieke Widhiantika; Yasin Azhari; Wendi Darmawan (Bajang Institute, 2023)
The implementation of ergonomics in the workplace is a key strategy to improve the health and productivity of workers, especially in the healthcare sector. This study aims to explore the impact of ergonomic working positions on the productivity of administrative staff at the Islamic Hospital of Karawang. A quantitative approach with a descriptive-analytic design was used, involving 100 administrative staff as respondents. Data were collected through questionnaires and direct observations of working conditions before and after ergonomic interventions. The data were analysed using paired t-tests to evaluate significant changes in work productivity and health complaints. The results show that good ergonomic practices can reduce complaints of back pain by 50%, neck pain by 30%, and circulatory problems by 10%. Additionally, there was an increase in job satisfaction by 25% and operational efficiency by 20% following the ergonomic interventions. A 20% reduction in absenteeism was also identified as a positive impact of the ergonomic interventions. These findings suggest that ergonomic working positions positively impact not only physical health but also enhance productivity and work efficiency. Therefore, ergonomics should be prioritized in human resource management in hospitals and other healthcare facilities. This study provides significant contributions to the development of evidence-based occupational health policies and can serve as a guideline for other hospitals to adopt better ergonomic practices. Thus, this study is expected to promote healthier, more productive, and more sustainable work environments in the healthcare sector